Analisis Beban Kerja dan Lingkungan Kerja Karyawan Packing PT. X Menggunakan Workload Analyisis dan NASA-TLX - Daniel Daniel; Desribeth Palullungan (Universitas Bunda Mulia, 2021)
Human resources (HR) take an important role in a company to improve product quality. Human Resources in terms of the number of people and skills possessed are factors that influence the production of quality goods/products. Productive workers are workers who are able to produce products or services in accordance with the quality that has been set in a short time. The problem with PT.X in the packing section is that the packing target has not been achieved as set by the company. Another problem is the presence of manual loads above the standard load set. Meanwhile, packing workers also complained about the hot working conditions. So that further analysis is needed to determine the physical and mental workload on the packing work of PT. X uses Workload Analysis and NASA-TLX as well as analysis of the physical work environment (temperature and lighting). The workload and conditions of the physical work environment experienced by workers will affect worker productivity. The results obtained based on measurements using the Workload analysis (WLA) method showed that the physical workload of the three employees was high with a value of 121.97%, 119.20%, 117.81%. The results of measurements using NASA-TLX indicate that the mental workload experienced by packing workers is overloaded with values of 80.67, 82.67, 80 respectively. lux, both are within the normal threshold according to the Ministry of Health standards.